The Future of TV opportunities IPTV is facilitating for novel revenue streams - Insley, Matthew James (2007)
IPTV (Internet Protocol TeleVision) is being hailed by industry experts as the "future of television" and as such this dissertation looks into the business environment within which it operates. Seminal literature in the business field was reviewed to yield concepts that facilitated analysis of IPTV and the stakeholders therein. Using the internet as a transmission medium to broadcast media was found to present a unique set of opportunities and threats that differ from traditional TV transmission mediums. The opportunity for a novel revenue stream based around increased targeting of adverts within the programming was found through primary and secondary research. This increased targeting is made possible due to the customisation and break from linear programming that IPTV already facilitates. The crux of the novel revenue stream comes from customising the advertising that users of IPTV see by utilising information about the users. Primary research has shown that people are not adverse to the concept of volunteering increased amounts of information for the purpose of targeting adverts, especially when incentives such as reduced price were given.